Pengaruh Kebijakan Pendanaan, Deviden dan Profitabilitas Perusahaan terhadap Set Kesempatan Investasi (IOS) - Akhmad Adi Saputro; Lela Hindasah (Journal of Accounting and Investment, 2007)
The objective this research is to examine financing policy, dividend policy and profitability of the  firm association investment  opportunity set. The sample of this study consist  of 28 firm in Jakarta Stock Exchange period 1999-2004. Common factor analysis is conducted to constructcomposite  measures then ranked to classify the growth of sampling firm. To examine the impact of the financing policy, dividend policy, and profitability to the  investment opportunity set of the high and low growth firm is used logit regression analysis. The result indicates that the impact between  financing policy, proxied  by Book value  of debt  to equity, Market value of debt to equity to investment  opportunity set, is significantly negative. The impact between  dividend policy  proxied  by dividend yield  and investment opportunity set is significantly negative, but dividen pay out ratio is not  significant. The impact of profitability, proxied  by return on assets to investment opportunity set is significantly positive.